2017
DOI: 10.1515/jms-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Gaming Behavior among Military Peacekeepers – Exploring the Role of Boredom and Loneliness in Relation to Gaming Problems

Abstract: The aim of the current study was to explore gaming problems in post-deployment veterans and to investigate whether boredom and loneliness can predict levels of gaming problems. The general well-being of veterans post their deployments to war zones is linked to an array of negative health consequences, and veterans may be at risk for developing gaming problems after homecomings. Problems that may be related to engagement in gaming include coping with negative emotions, such as boredom and loneliness, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…The mediation models tested were all informed by previous research suggesting that gaming motives are linked to GD and that they mediate the relationship between psychopathological symptoms and GD [14,24,31,54,55,56]. Overall, the findings corroborated the existing evidence suggesting that gaming motives play an important role in mediating the relationship between psychopathological symptoms (such as depression [57], loneliness [58] and attention problems [59]) and GD even when analyzed according to different diagnostic frameworks for GD. Taken together, the mediation analyses indicated that gaming motives play an important role in mediating the relationship between several psychopathological symptoms and GD regardless of the diagnostic framework employed to diagnose GD.…”
Section: Discussionsupporting
confidence: 69%
“…The mediation models tested were all informed by previous research suggesting that gaming motives are linked to GD and that they mediate the relationship between psychopathological symptoms and GD [14,24,31,54,55,56]. Overall, the findings corroborated the existing evidence suggesting that gaming motives play an important role in mediating the relationship between psychopathological symptoms (such as depression [57], loneliness [58] and attention problems [59]) and GD even when analyzed according to different diagnostic frameworks for GD. Taken together, the mediation analyses indicated that gaming motives play an important role in mediating the relationship between several psychopathological symptoms and GD regardless of the diagnostic framework employed to diagnose GD.…”
Section: Discussionsupporting
confidence: 69%
“…More specifically, GD, loneliness, and depression were examined within a bi-directional association pattern when controlling for weekly time spent gaming, age, and gender effects. This rationale was informed by previous empirical research suggesting that GD, loneliness, and depression are consistently implicated at the cross-sectional level (e.g., Burleigh et al 2018;Lee et al 2018;Lemmens et al 2015;Myrseth et al 2017;Pontes 2017). More specifically, these studies reported a positive association between these constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a focus on the importance of social and role functioning in psychological well-being, gamers themselves believe that interference with life areas, including avoidance of social interactions, is a primary indicator of gaming-related problems (Colder Carras et al, 2018a). Among military gamers, problematic play is not associated with loneliness or coping when pursuing positive feelings and avoiding boredom are controlled for (Myrseth et al, 2017). Clearly, commercial video games show the potential to help veterans, but it is also necessary to investigate factors that might create additional problems.…”
Section: Introductionmentioning
confidence: 99%